2018
DOI: 10.1007/s00592-018-1217-9
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and fear of diabetes-related long-term complications in people with type 2 diabetes at primary care level

Abstract: Prevalence of diabetes-related long-term complications was overestimated in people with diabetes type 2. Approximately one third of the participants showed even great fear. Patient expectation and fear about diabetes-associated complications did not correspondent with data on clinical reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…More than one third of the study participants showed significant fear of developing long-term complications. These results are in line with a previous study by Kuniss et al (2018) supporting that the prevalence of diabetes-related long-term complications was overestimated by people with DM2 at primary care level [10].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More than one third of the study participants showed significant fear of developing long-term complications. These results are in line with a previous study by Kuniss et al (2018) supporting that the prevalence of diabetes-related long-term complications was overestimated by people with DM2 at primary care level [10].…”
Section: Discussionsupporting
confidence: 93%
“…However, concrete numbers regarding prevalence and risks of these complications are not communicated within these programmes. A previous study by Kuniss et al (2018) showed that prevalence of diabetes-related long-term complications were overestimated by people with DM2 at primary care level, and approximately one third of the participants showed elevated fear of complications [10]. The trial by Meltzer et al (2000) confirmed this overestimation in people with DM1 [11].…”
Section: Introductionmentioning
confidence: 96%
“…And, while fear-based messages can be motivating, they may not be ideally suited for promoting positive diabetes-related behavior changes [32]. First, there may be limits to the level of fear that is motivating, and past work has demonstrated many individuals already fear disease-related complications and actually overestimate their risk for these outcomes [33][34][35][36]. Also, for fear to effectively shift behaviors, individuals need to know what actions to take to prevent the feared outcomes, information that was not included with the tested formats [33].…”
Section: Discussionmentioning
confidence: 99%
“…In Netherlands, people with T2DM and cardiovascular diseases follow a cognitive behavioral program aimed at modifying dietary behavior, physical activity, smoking behavior and its used methods as motivational interviewing and problems solving treatment focusing on intrinsic motivation for change and self-management 52 . The absolute risk of diabetes -related long -term complications (neuropathy, nephropathy, retinopathy, amputation, dialysis, blindness, stroke, coronary sclerosis) is not communicated and therefore often overestimated by patients, public health media, and health care professionals 53 . The study carried out in the United Arab Emirates (n = 490) reported that the prevalence of T2DM was 23% with hypertension, obesity, and dyslipidemia being the most common T2DM comorbidities and found that levels of estimated glomerular filtration rate and disease duration were the most significant risk factors for the development of complications 54 .…”
Section: Discussionmentioning
confidence: 99%